COVID 19 : Impact on mental health of graduating and post graduating students. Issue 1 (2nd January 2021) - Kumari, Pratibha; Gupta, Prateek; Piyoosh, Atul Kant; Tyagi, Babita; Kumar, Parvin
Abstract: The Corona Virus Disease (COVID-19) has emerged as an epidemic and created devastating impacts on people by infecting them throughout the world. To safeguard human lives from COVID-19, many countries have announced lockdown for all types of activities, and people have been advised to stay at home. In India, the nationwide lockdown has created a serious matter of concern in all sectors. The education sector is also facing challenges due to this disease. In this study, a psychological impact of COVID-19 on graduating and post graduating students has been assessed. An online survey was conducted, using an organized questionnaire with a cluster and simple random sampling method for students to assess their status of mental health in terms of the level of panic, worry and anxiety experienced by them. Further, the obtained mental health status was attributed to various reasons such as listening to related news, thinking of pandemic, discussion about the pandemic, future insecurities, and the impact of social media. The statistical data revealed the fact that students were mostly found worried due to future insecurities. Thus, there is an identified need of taking measures to reduce anxieties, worries and panic to help and reduce the complexities of mental health of students. Finally, an approach relevant to this need is also proposed which may help the students to fight against the devastating mental health impact of this pandemic.